Penggunaan Media E-Comic dalam Microteaching untuk Mengoptimalkan Pembelajaran Siswa Sekolah Dasar - Eliezer Sembiring; Aditiya Fadilah Gultom; Alyssha Cathleen Yucaary; Hafizha Nahdiyatul Haq; Nurmayani Nurmayani (Jurnal Merah Putih Sekolah Dasar, 2026)
This study aims to examine the use of e-comic media in microteaching practices to optimize learning among elementary school students. This study employs a Research and Development (R&D) approach using the ADDIE model, which includes the analysis, design, development, implementation, and evaluation stages. The resulting product is an interactive digital e-comic learning medium integrated with the local culture of North Sumatra and accessible via a flipbook platform. The results indicate that the e-comic medium has a very high level of feasibility. The use of e-comics is able to increase learning motivation, conceptual understanding, and student engagement through engaging visual and narrative presentations. Additionally, this medium also helps prospective teacher students in developing creativity, digital literacy, and innovative teaching skills in microteaching activities.